Antimicrobial peptide-targeted photodynamic therapy for preventing periodontal plaque biofilm formation through the disruption of quorum sensing system - Wen Li; Fengqun You; Jie Yang; Deao Gu; Yuyang Li; Xuan Zhang; Leiying Miao; Weibin Sun (Materials Today Bio)
Owing to high rates of antibiotic resistance, the elimination of periodontal plaque biofilms has become a significant clinical challenge. In this context, metal–organic framework (MOF)-based photodynamic therapy (PDT) has emerged as a novel antimicrobial treatment option. However, this therapeutic strategy suffers from drawbacks such as the insufficient generation of reactive oxygen species and the lack of targeted biofilm clearance, which greatly hinder its clinical application. Here, a multifunctional MOF-based nanocomposite (ICG@Uio-66-UBI) was developed by modifying MOFs (Uio-66-NH2) with an antimicrobial peptide (UBI29-41) to enhance PDT efficiency. Our findings showed that the UBI29-41 targets EPS and selectively binds to lipopolysaccharide (LPS) on bacterial surfaces via electrostatic interactions, enabling precise delivery of ICG-generated ROS under 808-nm near-infrared irradiation, which disrupts bacterial membranes and inhibits biofilm formation. Subsequently, UBI29-41 blocks LPS-TLR4 binding, suppressing NF-κB signaling and reducing pro-inflammatory cytokine production. Furthermore, the nanocomposite significantly downregulates the LuxS/AI-2 quorum sensing (QS) system, reducing AI-2 synthesis and virulence gene expression, thereby inhibiting biofilm formation. In vivo studies confirmed the platform's efficacy in inhibiting biofilm formation and preventing collagen degradation in gingival tissue. By synergistically combining targeted antimicrobial action, anti-inflammatory effects, and QS modulation, ICG@Uio-66-UBI represents a breakthrough in precision periodontal therapy, offering a potent solution for biofilm-associated infections.